基于MATlAB的液力变矩器的热仿真分析 - 吴新; 连晋毅 (Jixie chuandong)
According to the excessive heat of hydraulic mechanical transmission,heating mechanism on torque converter is explained.With a certain type of torque converter in bulldozers,the relationship between heat production and transmission ratio is described by Matlab programing,which on the basis of thermal analysis model.Meanwhile,the oil temperature on different ratio can be simulated by simulink,the result reflects the dynamic changing trend of hydraulic oil temperature.It will provide some technical reference for the analysis of chassis oil cooling system.